2020
DOI: 10.1186/s12885-020-07139-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus on survival in patients with gallbladder Cancer: a systematic review and meta-analysis

Abstract: Background: Increasing evidences indicated that diabetes might increase the incidence of gallbladder cancer. However, no sufficient data has ever clarified the impact of diabetes on the survival of patients with gallbladder cancer. Methods: We comprehensively searched PubMed, Embase, and the Cochrane Library databases through July 2019 in order to find sufficient eligible researches. The pooled hazard risks (HRs) and relative risks (RRs) with 95% confidence intervals (CIs) were calculated with either fix-effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…Systematic reviews have indicated that patients with diabetes had an increased risk of GBC and a higher GBC-mediated mortality compared with non-diabetic individuals. 34,35 In addition to CEA and CA199, 36 we found that CA724 may be a potential biomarker for GBC. However, in this study, there were too many missing data points, and we are prospectively collecting relevant results to obtain stronger evidence for CA724 as a potential biomarker.…”
Section: Discussionmentioning
confidence: 79%
“…Systematic reviews have indicated that patients with diabetes had an increased risk of GBC and a higher GBC-mediated mortality compared with non-diabetic individuals. 34,35 In addition to CEA and CA199, 36 we found that CA724 may be a potential biomarker for GBC. However, in this study, there were too many missing data points, and we are prospectively collecting relevant results to obtain stronger evidence for CA724 as a potential biomarker.…”
Section: Discussionmentioning
confidence: 79%
“…Gallbladder cancer (GBC) is the most common malignant tumor of the biliary tract. Although it is relatively rare, its median survival rate is only about 6 months (119). Deoxycholic acid (DCA) is down-regulated in GBC.…”
Section: Gallbladder Cancermentioning
confidence: 99%
“…Увеличение затрат на лечение данного дорогостоящего заболевания ложится экономическим бременем как на финансовые расходы государств, так и на самих пациентов. Все это подчеркивает необходимость дальнейшего определения стратегии скрининга факторов риска, а также разработки дополнительных мер по снижению распространенности и смертности от СД2 [1].…”
Section: обоснованиеunclassified